2014
DOI: 10.1017/s003329171400275x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depression co-morbidity and treatment on quality of life in patients with acute coronary syndrome: the Korean depression in ACS (K-DEPACS) and the escitalopram for depression in ACS (EsDEPACS) study

Abstract: Depression was significantly associated with worse QoL even in patients with recently developed ACS. Depression treatment was associated with QoL improvement in ACS patients in the 24-week treatment period, the effects of which extended to 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Depression was significantly associated with worse quality of life (QoL) even in patients with recently developed ACS. Depression treatment with escitalopram was associated with significant QoL improvement over the 24‐week treatment period, the effect of which extended to 1 year …”
Section: Treatment Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression was significantly associated with worse quality of life (QoL) even in patients with recently developed ACS. Depression treatment with escitalopram was associated with significant QoL improvement over the 24‐week treatment period, the effect of which extended to 1 year …”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Depression treatment with escitalopram was associated with significant QoL improvement over the 24-week treatment period, the effect of which extended to 1 year. 60 Using a U.K. general-practice research database, 1651 cases of upper gastrointestinal (GI) bleeding and 248 cases of ulcer perforation were found between April 1993 and September 1997 among patients aged 40-70 years and 10,000 matched controls. Exposure to SSRIs was observed in 3.1% of patients with GI bleeding but in only 1% of controls, with an adjusted RR = 3 (95% CI, 2.1-4.4).…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…In patients with ACS, comorbid depression is associated with poorer quality of life [82]. Therefore, given that CC has a better effect than CAU on depression, the fact that depression treatment in ACS has a known favourable prognostic effect on cardiac outcomes [83], and the fact that CC has a positive effect on physical outcomes, CC should be considered a good treatment option in ACS.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Although more procedures make CC more costly, several studies have shown that CC improves quality of life for 14 acceptable additional costs [38,75]. This has been shown to be the case for depression comorbid with various chronic medical conditions [76][77][78][79][80][81].In patients with ACS, comorbid depression is associated with poorer quality of life [82]. Therefore, given that CC has a better effect than CAU on depression, the fact that depression treatment in ACS has a known favourable prognostic effect on cardiac outcomes [83], and the fact that CC has a positive effect on physical outcomes, CC should be considered a good treatment option in ACS.…”
mentioning
confidence: 99%
“…It has been also shown that escitalopram can reduce the risk of post-ACS depression and improve quality of life among patients with ACS and depression (64,65). However, there is a possibility of SSRI increasing the risk of bleeding events, especially if used concurrently with nonsteroidal anti-inflammatory drugs or aspirin (9,66).…”
Section: Pharmacotherapymentioning
confidence: 99%